To Systematically Evaluate and Analyze the Efficacy and Safety of Transcatheter Arterial Chemoembolization (TACE) in the Treatment of Primary Liver Cancer. (21st March 2022) - Yang, Xiao; Lan, Tingting; Zhong, Hui; Zhang, Zujian; Xie, Hui; Li, Youwei; Huang, Wen
Abstract : The efficacy and safety of transcatheter arterial chemoembolization (TACE) are systematically evaluated in the treatment of primary liver cancer, which provides a reference for clinical practice and more in-depth research. Cochrane Library, PubMed, EMbase, CBM, CNKI, VIP, and WanFang Data, supplemented by other searches, collected all randomized controlled trials (RCT) comparing TACE combined with TACE alone for HCC. The meta-analysis, after selecting the literature, extracting data, and evaluating the methodological quality of the included studies following the inclusion criteria, was performed using RevMan 5.1 software. There was statistical difference in 3-year survival rate of TACE combined with heat treatment for advanced hepatocellular carcinoma (OR = 1.72, 95%CI (1.22, 2.41), P = 0.002, I 2 = 0%, and Z = 3.12), total effective rate (OR = 1.91, 95%CI (1.31, 2.78), P = 0.0008, I 2 = 0%, and Z = 3.37), quality-of-life improvement rate (OR = 2.29, 95%CI (1.62, 3.23), P < 0.00001, I 2 = 83%, and Z = 3.37), and complication rate (OR = 2.29, 95%CI (1.62, 3.23), P < 0.00001, I 2 = 83%, and Z = 3.37). Compared with TACE alone, TACE combined with hyperthermia can significantly improve the survival rate and recent efficacy of patients, improve the quality of life, and have a trend to reduce the incidence of toxicity. However, its long-term efficacy and more comprehensive safety need to be verified by more sample and high-quality RCT.